قياس مدى رضا قطاع الاعمال عن خدمات الشركة العالمية للاتصالات : دراسة ميدانية - سويدان، نظام موسى; سالم، محمد (جامعة البترا الخاصة, 2012)
هدفت الدراسة الي استكشاف , وتحليل , مدي رضا قطاع الأعمال عن الخدمات التي تقدمها الشركة العالمية للاتصالات, فيما اذا كان هناك توافق بين ما تقدمه هذه الشركة من خدمات وبين توقعات زبائنها, وهل هناك عجوة أداء بين المتوقع والواقع . كما سعت الدراسة الي التعرف علي المشكلات التي تعيق تحقيق درجة الرضا من قبل المستفيدين, ولتحقيق هذه الأهداف وزع الاستبيان علي عيه عشوائية باستخدام: النسب المئوية, تحليل التباين ANOVA , واختبار t-test. \ وقد توصلت الدراسة الي عدد من الاستنتاجات أهمها :هناك درجة رضا عام عن خدمات الشركة, مع وجود سلبيات من وجهة النظر التسويقية الاستراتيجية. والادراك والوعي الكامل لقطاع الأعمال لأهمية الانتشار والتوسع في المنطقة الإقليمية بهدف تحسن موقفه التنافسي, ولهذا فهو بحاجة الي كل ما هو جديد في تكنولوجيا الاتصالات سواء في السوق المحلي أو الخارجي. \ واعتماداً نتائج الدراسة, أوصت بضرورة التنبه لأهمية الاصغاء للزبائن واستحدثت نظام فاعل وطاقم مدرب للتعامل مع شكاوي المستفيدين, ضرورة تبني الشركة لعدة مفاهيم حديثة لبناء قدراتها التنافسية في السوق كمفهوم التسويق بالعلاقات , والتسويق الداخلي, والجودة الشاملة, وضرورة اعتماد تقديم الشركة لمنتجاتها علي أساس الحزمة BACKAGE بهدف خفض تكاليفها الثابتة وتقوية موقفها التنافسي. This study aimed at discovering and analyzing the extent of the business sector satisfaction on the services provided by Global Telecommunication Co. and whether there was a match between what the company provides and their customer expectations, is there a performance gap between what is expected and reality. To achieve these goals a questionnaire was distributed , whereby a simple random sample of (180) companies were chosen and (146) of which were statistically processed. The data that undergone statistical processing using: percentages, one way ANOVA, and one sample T-Test. \ The main findings of the study are as follows: (1) There is a general satisfaction concerning the company services, with the presence of negatives that are considered serious from the strategic marketing point of view, and (2) The full awareness by the business sector for the diversification in the region to improve its competitive situation,. Depending on the study findings, the researchers provided a number of recommendations: The importance of listening to customers and to develop an effective system and well-trained staff to deal with beneficiaries complains, and the importance of adopting many new concepts by the company (i.e, relationship marketing, internal marketing, and total quality) to build its competitive capabilities in a market, and to build medium-term strategy to deal with different segments of beneficiaries, the importance of introducing its products on the basis of (PACKAGE) in order to decrease its fixed costs, and strengthening its competitive edge
1 - ملخص لبحث منشور باللغة الانجليزية
Keywords: التسويق الداخلى -- مستخلصات الابحاث -- الشركة العالمية للاتصالات -- خدمات العملاء -- رضا العملاء -- استراتيجية التسويق